ANALISIS PENGARUH INFORMASI AKUNTANSI TERHADAP HARGA SAHAM DENGAN LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSBILITY SEBAGAI PEMODERASI - Aditya, Tony (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2016)
Value relevance is being defined as the ability to explain the effect of accounting information to the price or stock returns. Accounting information is relevant if it could affect users of the financial statements in making decision. Earnings, book value, and cash flow constitute important components of financial report which is usually used as a means to inform the company’s performance. Aside from financial report, accounting information can also be obtained from on corporate social responsibility disclosure report. The objective of this research is to analyze the relevance of accounting information included earnings, book value, and cash flow to the stock price and to test the role of corporate social responsibility disclosure in moderating the relevance of earnings and book value. Sample that used in this research is non-financial listed companies in Indonesian Stock Exchange on 2007-2011. Samples are determined by purposive sampling method, 505 for the first sampling and 235 for second sampling. Hypotheses were tested using multiple regression analysis. This research shows that earning, book value, and cash flow from operating activity and cash flow from investment have value relevance, on the other hand financing is proven has no relevance with stock price. CSR Disclosure has been proven that it can moderate the relevance of earning and book value.